Analysis of Foreign Tourists' Perceptions of the Quality of Tourism in West Nusa Tenggara - Lalu Mohamad Iswadi Athar (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2022)
Purpose: This study aims to look at the assessment of foreign tourists on tourism conditions in Nusa Tenggara. Method: This study used a layered random sampling technique and a five-point Likert Scale. Result: According to this study, foreign tourists in West Nusa Tenggara had positive perceptions of the region's accessibility, destination allure, range of attractions, information, friendliness, cleanliness, lodging, and reasonable rates. Contribution: This research provides an overview for tourism managers, both private, government, and other stakeholders related to the quality of tourism in the eyes of foreign tourists